Analysing oil price- macroeconomic volatility in Nigeria - Alhassan Abdulkareem; Kilishi A. Abdulhakeem (CBN Journal of Applied Statistics, 2016)
This study provides analytical insight on modelling macroeconomic and oil price volatility in Nigeria. Mainly, the paper employed GARCH model and its variants (GARCH-M, EGARCH and TGARCH) with daily, monthly and quarterly data. The findings reveal that: all the macroeconomic variables considered (real gross domestic product, interest rate, exchange rate and oil price) are highly volatile; the asymmetric models (TGARCH and EGARCH) outperform the symmetric models (GARCH (1 1) and GARCH - M); and oil price is a major source of macroeconomic volatility in Nigeria. By implication, the Nigerian economy is vulnerable to both internal shocks (interest rate volatility, real GDP volatility) and external shocks (exchange rate volatility and oil price volatility). Therefore, it is concluded that more credence should be given to asymmetric models in dealing with macroeconomic volatility in Nigeria and oil price volatility should be considered as relevant variable in the analysis of macroeconomic fluctuations in Nigeria. The study recommends that, the Nigerian economy should be diversified by revamping other sectors such as the agricultural sector and the industrial sector in order to reduce the impact of oil price uncertainty on macroeconomic volatility.
Keywords: C22; C58; E43; 330; Volatility; Oil Price; Real GDP; Exchange Rate; Interest Rate; GARCH Models